An integrated energy performance-driven generative design methodology to foster modular lightweight steel framed dwellings in hot climates - Rodrigues, Eugénio (2018)
This paper presents a study on the application of lightweight steel framed (LSF) construction systems in hot climate. A generative design method created 6010 houses, with random geometry and random roof and exterior wall types with different insulation levels, and EnergyPlus was used to evaluate the energy consumption for air-conditioning of each building. The main goals were to determine which geometric variables correlate with the energy performance, and to provide some guidelines to foster efficient LSF buildings in hot climates. By correlating six geometry-based indexes with the energy consumption for each construction element type group, it was verified that roofs do not show significant correlation, while exterior walls presented weak to moderate positive correlation with the building volume, very weak to weak negative correlation with the relative compactness, no correlation with the shape coefficient, moderate to strong negative correlation with the window-to-floor, window-to-wall, and window-to-exterior surface ratios. The results also show that buildings with larger windows and greater level of insulation have better energy performance. No significant difference of energy performance was found between different LSF construction systems with equivalent thermal resistance.